2010
DOI: 10.1088/0953-8984/22/35/355801
|View full text |Cite
|
Sign up to set email alerts
|

High pressure orthorhombic structure of CuInSe2

Abstract: The structural behaviour of CuInSe(2) under high pressure has been studied up to 53 GPa using angle-dispersive x-ray powder diffraction techniques. The previously reported structural phase transition from its ambient pressure tetragonal structure to a high pressure phase with a NaCl-like cubic structure at 7.6 GPa has been confirmed. On further compression, another structural phase transition is observed at 39 GPa. A full structural study of this high pressure phase has been carried out and the high pressure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
(24 reference statements)
1
11
0
3
Order By: Relevance
“…The P4/mmm space group obtained from Fm3m that can distinguish Cu and In sites in the primitive cell. These results confirm the experiments and calculations studies [10][11][12], but we can distinguish the Cu and Ga sites in Fm3m and Cmcm to the P4/ mmm and Amm2, respectively. At the transition pressure 52 GPa (P4/mmm to Amm2), the equilibrium point in cubic phase (P4/ mmm) was pressed, and changed to orthorhombic space group (Amm2) as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The P4/mmm space group obtained from Fm3m that can distinguish Cu and In sites in the primitive cell. These results confirm the experiments and calculations studies [10][11][12], but we can distinguish the Cu and Ga sites in Fm3m and Cmcm to the P4/ mmm and Amm2, respectively. At the transition pressure 52 GPa (P4/mmm to Amm2), the equilibrium point in cubic phase (P4/ mmm) was pressed, and changed to orthorhombic space group (Amm2) as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Atomic coordinates at 0 GPa of Cu, Ga and Se are (0, 0, 0), (0, 0, 0.5) and (0.244, 0.25, 0.125), respectively. In previous experiments [7][8][9][10], it has been suggested that Fm3m and Cmcm structures are the thermodynamically stable phases of CuInSe 2 and CuGaSe 2 beyond the ambient phase (I42d), and atomic positions of Cu and Ga are not distinguish both Fm3m and Cmcm. In this calculation, we imposed the lower symmetry space groups on Fm3m and Cmcm structures which the Cu and Ga atomic positions are distinguish, so that it can be optimized by geometry optimization.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Die Gitterparameter bei Standardbedingungen betragen a=5.7820(2) Å und c=11.6173(4) Å, jedoch sind Schwankungen der Parameter durch nichtstöchiometrische Elementzusammensetzung bekannt [59]. Bei einem Druck von 6 bis 8 GPa ( [81], [25], [84], [92], [8]) erfolgt eine Umwandlung in den NaCl-Typ mit einer angenommenen zufälligen Verteilung der Kationen und einer Reduktion des Elementarzellenvolumens um 17% (siehe Abbildung 3.3). Die Koordinationszahl steigt von 4 nach 6.…”
Section: Cadmiumselenid (Cdse)unclassified
“…Eine Elementanalyse des verwendeten Probenmaterials mit der Elektronenstrahl-Mikrosonde ergab eine Zusammensetzung aus 24.98 (8) 2. Kleine Vierschraubenzelle nach modifiziertem Merrill-Bassett-Typ [47] mit Diamantsitz aus Beryllium (siehe Abbildung 4.2a).…”
Section: Cadmiumselenid (Cdse)unclassified